Pro CSS Techniques - Croft, Jeff (Apress, 2012)
This book is a collection of proven, professional, modern techniques that you can use every day to get the most out of the time you put into your projects, from start to finish. As it has finally come to pass that CSS (Cascading Style Sheets) and other web standards are useful, real-world tools as opposed to idealistic goals, more and more professional web developers are moving to CSS from older approaches. Web browsers that support CSS well are now the default for the vast majority of web surfers. Additionally, a whole new generation of web developers are appearing on the scene, many of whom have never had the grave displeasure of dealing with nested table layouts and spacer GIFs.